Quality Assessment Method for Chromite Sand to Reduce the Number of Cast Steel Surface Defects - T. Wróbel; J. Jezierski; D. Bartocha; E. Feliks; A. Paleń (Archives of Foundry Engineering)
This paper discusses the ability to apply the test method using a scanning electron microscope (SEM) together with EDS (Energy Dispersive Spectroscopy) analysis to assess the quality of fresh chromite sand delivered by various suppliers to Huta Małapanew Sp. z o.o. The research was initiated due to the non-cyclical occurrence of surface casting defects, i.e. pitted skin and burn-on of chromite moulding sand for cast steel casting. The scope of studies comprised the quality assessment of sixteen chromite sand batches delivered for six months by two suppliers. The analysis of the results obtained was used to describe components of the tested chromite sand batches and develop criteria for their quality assessment, considering the chemical composition of chromite grains and the amount of impurities in the form of silica sand and the binder particles. Moreover, clear suggestions were developed concerning the ability to use the given chromite sand batch as the base of moulding sand made in Alphaset technology in Huta Małapanew Sp. z o.o.